ANALYSIS OF THE CORRESPONDENCE OF THE ROAD NETWORK OF THE OPISHNIAN TERRITORIAL COMMUNITY TO THE DEVELOPMENT TENDENCIES OF THE WASTE MANAGEMENT SYSTEM IN THE REGION - BREDUN, Viktor; MYKOLAICHYK, Тaras (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Planning of effective waste management systems at the level of territorial communities is an important practical task that ensures the implementation of the overall regional concept of the development of the regional waste management system. This process is based, first of all, on the study of the scientific and practical foundations of forecasting trends in the development of waste management systems, and especially their logistical component, taking into account the specifics of regional factors. Thus, there is a need to conduct an analysis of the technical-logistic component of the waste management system of individual territorial communities and its development prospects as a component of the regional waste management system of the Poltava region within the framework of solving the current scientific and practical task of ensuring the effectiveness of the implementation of the regional waste management system. Methodology. When studying the structure and technological parameters of the elements of the road network included in the project routes of solid waste transportation, the methods of system and factor analysis were used. Results. It has been established that the road network of Opishnyan TС is simultaneously an element of the logistics structure of the waste management system at the local and regional level and is involved in all stages of solid waste transportation during various periods of implementation of the Regional Waste Management Plan of the Poltava Region. All categories of roads are involved in the transport schemes. The roads of the fourth category and some roads of the 5th category are the most heavily loaded. Most roads of categories T, O, C are in unsatisfactory condition and need urgent repair. The capacity of the existing road network, if it is maintained in a satisfactory condition, provides the possibility of movement along the specified routes of both collection and transport garbage trucks. The maximum permissible speed of movement according to the parameter of categorization on all roads of the region corresponds to the technical parameters and design modes of movement of specialized transport. Originality. The technological possibilities, main problems and directions of improvement of the road network of Opishnyan TС as a separate object of logistics planning and a structural component of the waste management system at the local and regional levels have been determined. Practical value. The technological possibilities, main problems and directions of improvement of the road network of Opishnyan TС as a separate object of logistics planning and a structural component of the waste management system at the local and regional levels have been determined.
Keywords: waste management system; logistics structure; road network; waste transportation; route